Knowledge, Attitude, and Behavior toward COVID-19 Prevention on Indonesian during Pandemic - Widowati, Retno; Raushanfikri, Albiruni (Open Access Macedonian Journal of Medical Sciences, 2021)
Objectives: To know the socio-demographic factor related to the knowledge, attitude and behaviour towards COVID-19 prevention, during the COVID-19 pandemic in Indonesia. Method: Research was conducted through observation with a cross-sectional approach and samples were collected using snowball sampling. The research population was the general Indonesian. The questionnaire was used and distributed online for four days. Chi-square and regression were used for analysis. Result: The questionnaire distributed was fulfilled completely by 1,167 participants from 30 provinces. Gender has a negative correlation with participants' attitudes and behaviour in preventing COVID-19. Age and education were significantly related (p <0.01) to COVID-19 knowledge and had a significant positive effect (p <0.01) on attitude and behaviour. The occupation was significantly related (p <0.01) to COVID-19 knowledge. Occupation has a positive effect, but not significantly on attitudes and behaviour. The province of the participants’ residence was not significantly related to COVID-19 knowledge, and it isn't significantly on attitude and behaviour. Knowledge has highly affected the attitude of preventing COVID-19 (f = 0.36). Conclusion: Age, education and occupation significantly related to COVID-19 knowledge. Age and education are positively correlated with attitude and behaviour. Knowledge has highly affected by the attitude of preventing COVID-19.